2005
DOI: 10.1128/iai.73.12.7869-7877.2005
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of OspC Type Diversity in Invasive Human Lyme Disease Isolates and Identification of Previously Uncharacterized Epitopes That Define the Specificity of the OspC Murine Antibody Response

Abstract: Outer surface protein C (OspC) of the Lyme disease spirochetes is an important virulence factor that has potential utility for vaccine development. Of the 21 OspC types that have been identified, it has been postulated that types A, B, I, and K are specifically associated with invasive infections. Through an analysis of isolates collected from patients in Maryland we found that OspC types C, D, and N are also associated with invasive infections. This observation suggests that there is greater diversity in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
140
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(146 citation statements)
references
References 41 publications
4
140
1
1
Order By: Relevance
“…The exclusive use of protective epitope sequences reduces the potential for misdirection of the response to irrelevant epitopes. In the context of OspC, this is particularly important as vaccination with full length r-OspC elicits immune responses to conserved domains that are not presented by the bacteria during infection [33,37,38]. In this study, we extend our efforts to develop and optimize a recombinant, polyvalent, chimeric OspC vaccinogen.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The exclusive use of protective epitope sequences reduces the potential for misdirection of the response to irrelevant epitopes. In the context of OspC, this is particularly important as vaccination with full length r-OspC elicits immune responses to conserved domains that are not presented by the bacteria during infection [33,37,38]. In this study, we extend our efforts to develop and optimize a recombinant, polyvalent, chimeric OspC vaccinogen.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant full length OspC proteins of types A, B, K and D (minus the leader peptides) were generated as previously described, using a PCR based approach and ligase-independent cloning (LIC) methodologies with the pET-32 Ek/LIC vector (Novagen) [17,33]. The DNA sequences of these and all other constructs described in this report were confirmed (MWG Biotech).…”
Section: Expression and Purification Of Recombinant Ospcmentioning
confidence: 99%
See 2 more Smart Citations
“…The OspC types of human clinical isolates have also been correlated with invasive and non-invasive phenotypes [128,131]. However, similar studies demonstrated greater diversity among invasive types than previously recognized, calling into question any causative effect of OspC sequence on invasion [130,132]. Carefully controlling for variables other than OspC has not been possible in such studies, since additional genome components of these isolates also differ.…”
Section: B Burgdorferi Products Required For Mammalian Infectionmentioning
confidence: 99%